Diffuse Hair Loss Induced by Sertraline Use - Kıvrak, Yüksel; Yağcı, İbrahim; Üstündağ, Mehmet Fatih; Özcan, Halil (Case Reports in Psychiatry, 2015)
Hair loss is a rare side effect of psychotropic drugs. The most related drug class with this side effect is the mood stabilizers. Studies reporting the sertraline-induced alopecia are limited in number. Sertraline is a potent antidepressant which inhibits the serotonin reuptake from the presynaptic terminals selectively. The reason for hair loss could not be elucidated completely. Psychotropic drugs are usually considered to lead to hair loss through influencing the telogen phase of hair follicle. This paper reports a 21-year-old male with diffuse hair loss induced by sertraline use and improved by quitting the drug. To the best of our knowledge, there are no other case reports on sertraline-induced alopecia within 2 weeks.